E-LEARNING W KSZTAŁCENIU KOMPETENCJI MIĘDZYKULTUROWYCH NA POZIOMIE UNIWERSYTECKIM – W STRONĘ KODEKSU DOBREJ PRAKTYKI - Półtorak, Ewa; Krajka, Jarosław (Neofilolog, 2018)
The purpose of the present paper is to describe selected self-study learning environments focused on target language culture for university students. After reviewing introductory concepts of intercultural competence, the results of the external audit of a corpus of e-learning courses will be presented. Conclusions reached may pave the way for future development of interactive materials for intercultural instruction.